2015
DOI: 10.1002/anie.201411403
|View full text |Cite
|
Sign up to set email alerts
|

Direct C(sp2)C(sp3) Cross‐Coupling of Diaryl Zinc Reagents with Benzylic, Primary, Secondary, and Tertiary Alkyl Halides

Abstract: The direct C(sp(2) )-C(sp(3) ) cross-coupling of diaryl zinc reagents with benzylic, primary, secondary, and tertiary alkyl halides proceeded in the absence of coordinating ethereal solvents at ambient temperature without the addition of a catalyst. The C(sp(2) )-C(sp(3) ) cross-coupling showed excellent functional-group tolerance, and products were isolated in high yields, generally without the requirement for purification by chromatography. This process represents an expedient, operationally simple method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 53 publications
0
33
0
Order By: Relevance
“…However, adding an equiv of MgCl 2 to this type of arylzinc reagent made the yield significantly increase to 83 % (Table , entry 3). It has been reported that action of ArZnX with MgX 2 led to formation of ionic zincates which have higher reactivity than ArZnX . The role of LiX may involve increasing the solubility of the zinc reagents through forming a trimetallic adduct and producing reactive zincates…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 78%
See 2 more Smart Citations
“…However, adding an equiv of MgCl 2 to this type of arylzinc reagent made the yield significantly increase to 83 % (Table , entry 3). It has been reported that action of ArZnX with MgX 2 led to formation of ionic zincates which have higher reactivity than ArZnX . The role of LiX may involve increasing the solubility of the zinc reagents through forming a trimetallic adduct and producing reactive zincates…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 78%
“…On the other hand, transition‐metal‐free reactions are attracting more and more attention because they are less costly and more environmentally friendly and can avoid any transition metal impurities in pharmaceutical products . For example, Hayashi et al.…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 99%
See 1 more Smart Citation
“…Unless otherwise indicated all reagents were purchased from commercial sources and were used without further purification. The zincate, [14] 4-bromo-7-(9,9-dioctyl-9H-fluoren-2-yl)benzo[c] [1,2,5]thiadiazole, [22] Pd(tBu 3 P) 2 , [23] 2-BPh 2 [8] bis(tri-n-butylstannyl)thieno[3,2-b]thiophene [24] were synthesised by modified literature procedures. All appropriate manipulations were performed by using standard Schlenk techniques or in an argon-filled MBraun glovebox (O 2 levels below 0.5 ppm).…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with Lemaire's work, this study also stresses that the success of the coupling heavily depends on the use of non-polar, non-coordinating solvents. [6] Thus, the presence of ethereal solvents such as THF or Et2O dramatically slows down the reactions,. [6] While these results illustrate the ability of arylzinc reagents to engage in cross-coupling without the need of transition-metal catalysis, no mechanistic information is available on how these reactions actually occur.…”
mentioning
confidence: 99%